INTERAKSI SOSIAL WARGA PERUMAHAN ALAM SEJAHTERA DEDY JAYA KELURAHAN PASARBATANG KABUPATEN BREBES - Mustofa, Bisri (Civic Education Program, Universitas Negeri Semarang, 2017)
Social interaction occurs when one individual does an action; thus, it creates reaction to other individuals. Social interaction is not only a form of cooperation, but it is also competition and conflict. Consequently, it can be stated that the interaction is the basis of a form of social interaction because if there is no social interaction, the activity of individual between another individual is not called as interaction. This activity becomes a basis that creates social interaction of inhabitants at Perumahan Alam Sejahtera Dedy Jaya. The purpose of this research are: 1) To determine social interaction of inhabitants at Perumahan Alam Sejahtera Dedy Jaya, Pasarbatang Village, Brebes Regency. 2) To determine the obstruction of social interaction of inhabitants at Perumahan Alam Sejahtera Dedy Jaya, Pasarbatang Village, Brebes Regency. This research used a qualitative approach. It was conducted at Perumahan Alam Sejahtera Dedy Jaya, Pasarbatang Village, Brebes Regency. The source of research data was taken from the board office of housing, the chairman of RW, the chairman of RT, the prominent figure of the society and the inhabitants. The focus of this research was the social interaction that could be seen from the forms of social interaction in carrying out such activities, RT meeting, Pos Ronda, mutual cooperation etc. The methods of data collection used observation, interview, and documentation. The results of the research that explained about social interaction at Perumahan Alam Sejahtera Dedy Jaya, basically they were formed because of the result of social activity among inhabitants. After the writer searched and observed deeply, the results of the research showed that the social interaction that occurs between inhabitants was through some forms of social interactions and they were classified in the process of cooperation, competition, accommodation, and conflict. The implementation in the field of social interaction that occurred between people was very good and the course of activity also happened very well; as a result, the activities at Perumahan Alam Sejahtera Dedy Jaya were accordance with the expectation from society, i.e. there was social interactions that maintain the relationship among inhabitants.